ANALYSIS OF THE INFLUENCE OF FINANCIAL TECHNOLOGY ON MSME INCOME IN SOUTH JAKARTA - Hendratni, Tyahya Whisnu (INQUISITIVE : International Journal of Economic, 2025)
The purpose of this study is to test the influence of digital finance on MSME income. Several activities have been carried out to conduct tests related to the concept of theory, the level of analysis that is relevant to the indicators used related to data processing taken from 200 MSME respondents in the South Jakarta area. The analysis technique used is SEM -PLS. The results of the study prove that the use of financial technology proxied by Financial Culture has a positive and significant effect on MSME income in the South Jakarta area. Financial Technology proxied by financial behavior has a negative and insignificant effect on MSME income in the South Jakarta area. The use of Financial technology proxied by Financial awareness has a positive and significant effect on MSME income in the South Jakarta area.